The Safety of Leafy Vegetables in Oman (American Journal of Food Science and Technology, 2024)
Leafy vegetables are potential carriers of foodborne diseases that threaten the community’s well-being. Therefore, monitoring leafy vegetable’s microbial and heavy metal contamination is crucial. This study evaluates the safety of leafy vegetables consumed in Oman by examining pathogenic bacteria such as Escherichia coli, Staphylococci, Salmonella, and Listeria, as well as the heavy metals concentration. Results indicate high levels of microbial contamination in all samples, exceeding the Gulf Standard Organization permissible levels for E. coli and Staphylococci. The highest levels of E. coli were 5.96, 6.08, 6.09, 6.25, and 6.01 log CFU/g in Arugula, Radish, Lettuce, Cabbage, and Spring onion, respectively. While for Staphylococcus the highest values were 5.59, 5.71, 4.33, 5.07, and 4.46 log CFU/g in Arugula, Radish, Lettuce, Cabbage, and Spring onion, respectively. No Salmonella or Listeria colonies were found in any samples even after several days of incubations. The Arsenic and Lead concentrations in all samples were significantly higher than the permissible levels set by FAO/WHO, while Chromium was high in some samples. The concentrations of Copper and Iron in most samples fell below their respective permissible levels, while Zinc was undetectable in all samples. These findings underscore inadequate hygiene, harvesting, storage, and agricultural practices, raising concerns about the health implications of consuming contaminated leafy vegetables.